2021
DOI: 10.1155/2021/8858326
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Long Noncoding RNAs as Potential Novel Biomarkers in Intrahepatic Cholestasis of Pregnancy

Abstract: Long noncoding RNAs (lncRNAs) are a class of important regulators participating in various pathological processes. Until now, the role of lncRNAs in the occurrence and development of intrahepatic cholestasis of pregnancy (ICP) has rarely been investigated. The data from microarray screening revealed 58 upregulated and 85 downregulated lncRNAs and 47 upregulated and 71 downregulated mRNAs in ICP patients compared to healthy controls. Bioinformatics analysis revealed biological processes focused on lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…3.1.3 Serum lncRNAs and fatty acid metabolism, cell cycle, apoptotic signaling, and the oxidative stress pathway Zou et al elucidated the expression profiles of lncRNAs by collecting the serum samples of patients with ICP and explored the diagnostic and prognostic values of the differentially expressed lncRNAs in ICP. They revealed that 58 lncRNAs were upregulated and 85 were downregulated in patients with ICP compared with healthy controls (S. Zou et al, 2021). Furthermore, to verify this finding, the expression of three lncRNAs, namely, ENST00000449605.1, ASO3480, and ENST00000505175.1, was measured.…”
Section: Linc02527 Promotes Autophagy In Icpmentioning
confidence: 90%
See 1 more Smart Citation
“…3.1.3 Serum lncRNAs and fatty acid metabolism, cell cycle, apoptotic signaling, and the oxidative stress pathway Zou et al elucidated the expression profiles of lncRNAs by collecting the serum samples of patients with ICP and explored the diagnostic and prognostic values of the differentially expressed lncRNAs in ICP. They revealed that 58 lncRNAs were upregulated and 85 were downregulated in patients with ICP compared with healthy controls (S. Zou et al, 2021). Furthermore, to verify this finding, the expression of three lncRNAs, namely, ENST00000449605.1, ASO3480, and ENST00000505175.1, was measured.…”
Section: Linc02527 Promotes Autophagy In Icpmentioning
confidence: 90%
“…Studies on the biological functions and roles of lncRNAs as potential ICP biomarkers are limited. Zou et al investigated the diagnostic and prognostic values of ENST00000449605.1, ASO3480, and ENST00000505175.1 in ICP, established ROC curves, and computed the AUCs values, which were 0.812, 0.798, and 0.731, respectively (S. Zou et al, 2021). When the three lncRNAs were combined, the AUC value increased to 0.865; this finding indicates that the combined use of these three lncRNAs is a more reliable diagnostic marker for ICP.…”
Section: Diagnostic Value Of Lncrnas In Icpmentioning
confidence: 99%
“…Up-regulation of CRH expression was used in treatment with UDCA in patients with ICP. The diagnosis of certain forms of hepatic impairment is a challenge due to either incomplete diagnostic criteria or specific criteria that overlap in several clinical conditions [17][18][19][20][21][22] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of ICP and laboratory markers, a series of new genetic markers have been proposed, with potential clinical utility. In ICP, some biomarkers are used for a correct diagnosis (long noncoding RNA, neopterin, maternal urinary mRNAs, and native thiol) and others in the evaluation of the treatment (CRH) [17][18][19][20][21][22] (Table 3).…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…lncRNAs played an important role in a variety of biological processes, such as cancer progression (Qi et al, 2021), inflammatory bowel disease (Jiang and Zhang, 2021), cell autophagy in breast cancer (Li et al, 2021a), and energy metabolism (Tan et al, 2021). Zhou and his colleagues noted that serum expression levels of three lncRNAs-ENST00000505175.1, ASO3480, and ENST00000449605.1 had diagnostic value for ICP patients (Zou et al, 2021). Hu et al (2018) indicated that there was an elevated expression of Linc02527 in the placenta and serum of ICP patients, and functional studies showed that Linc02527 enhanced the autophagy and proliferated the ability of HTR8 cells.…”
Section: Introductionmentioning
confidence: 99%